Analisis Yuridis Dampak Pencemaran Lingkungan Pertambangan Mangan dan Nikel di Provinsi Maluku Utara - Bidul, Sayang; Widowaty, Yeni (JUSTISI, 2023)
This study analyzes the impact of what happens to communities in North Maluku Province due to manganese and nickel mining. The purpose of this study is to determine what impacts occur on communities in North Maluku Province due to manganese and nickel mining and provide solutions to the research results. In contrast to previous research, this study focuses on the impacts that occur that harm the community and the concepts that should be done in dealing with it through a conflict resolution approach. This research is a Normative legal research. The results found that: The impact of Manganese and Nickel mining in North Maluku Province from the results of the author's research has a positive impact as an economic support and has a negative impact on the environment and according to the author is more likely to have many negative impacts, including: water pollution, air and soil pollution due to Manganese and Nickel mining activities in Central Halmahera Regency, North Maluku Province, according to the author, is a serious problem. The government's desire to make Indonesia as a major producer of Nickel-based products, the lives of the people of Central Halmahera in the Nickel mining area were deprived. They have to give up losing their livelihood until their health is compromised. There is no accountability from PT. IWIP for the impact that occurs is also influenced by the new applicable rules, namely Article 88 Article 88 of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation Being a law, where provisions without proving the element of guilt have been removed, this will make it difficult for the community to prove the impact of environmental pollution that occurs. Keywords: Impact of Environmental Pollution; Mining Accountability; Mining Conflict.